The One Quail Per Acre Myth - Forest E. Kellog; Gary L. Doster; Edwin V. Komarek Sr.; Ray Komarek (National Quail Symposium Proceedings, 2017)
Data are presented which conflict with the 1-bird-per-acre saturation point concept for bobwhites (Colinus virginianus). Conclusions are that if a saturation point exists it is at a level greater than 2 bobwhites per acre.